1996
DOI: 10.1111/j.1746-1561.1996.tb06253.x
|View full text |Cite
|
Sign up to set email alerts
|

Response of African‐American Adolescents in North Carolina to Gun Carrying by School Mates

Abstract: This study examined adolescents' perceptions concerning the presence of guns in their school and the adolescents' emotional and behavioral responses associated with these perceptions. Survey data from 376 African-American sixth, seventh, and eighth grade students of a low-income area of a North Carolina city were studied. Twenty-eight percent of adolescents reported that other students brought guns to school, 36% felt afraid that someone would hurt or attack them while at school, 15% avoided school (or places … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 13 publications
1
41
0
Order By: Relevance
“…Bowen, Richman, Brewster, & N.K. Bowen, 1998;DuRant, Kahn, Beckford, & Woods, 1997;Everett & Price, 1995;Malek, Chang, & Davis, 1998;Martin, Sadowski, Cotten, & McCarraher, 1996). The students' scholastic performance is important because, over the past century, criminologists have time and again documented an inverse relationship between educational attainment and criminal behavior (Duncan, 1931;Glueck & Glueck, 1950;Hirschi, 1969;Sampson & Laub, 1993).…”
Section: Additional Methodological Considerationsmentioning
confidence: 99%
“…Bowen, Richman, Brewster, & N.K. Bowen, 1998;DuRant, Kahn, Beckford, & Woods, 1997;Everett & Price, 1995;Malek, Chang, & Davis, 1998;Martin, Sadowski, Cotten, & McCarraher, 1996). The students' scholastic performance is important because, over the past century, criminologists have time and again documented an inverse relationship between educational attainment and criminal behavior (Duncan, 1931;Glueck & Glueck, 1950;Hirschi, 1969;Sampson & Laub, 1993).…”
Section: Additional Methodological Considerationsmentioning
confidence: 99%
“…This linkage has also been addressed in studies of high-school student fear. Such research indicates that students who express being fearful or having a heightened perception of risk associated with school are more likely to avoid attending school Bastian & Taylor, 1991;Lawrence, 1998;Martin et al, 1996;Pearson & Toby, 1991).…”
Section: Empirical Evidencementioning
confidence: 99%
“…Peer influence on weapon carrying has been inferred from the findings of previous research, showing that weapon carrying among adolescents is related to perceived weapon carrying of peers [6,7] or friends [4,8 -10]. However, in these studies, the weapon carrying by friends was reported by adolescents themselves, which potentially inflates the magnitude of similarities in behaviors and, consequently, influences processes.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has also been suggested that it is not so much being the initiator of aggression, rather it is being the target of aggression, that triggers weapon carrying as a defensive response [7,21]. Consistent with this perspective, weapon carrying has been associated with feelings of being threatened, such as victimization, fearfulness, and selfprotection [7,[21][22][23][24].…”
mentioning
confidence: 98%
See 1 more Smart Citation